Various prosthetic treatment options in complete edentulous patients with xerostomia: A literature review - Sareh Habibzadeh; Mina Khayamzadeh; Asal Moravej; Afagh Tavasoli (Tehran University of Medical Sciences, 2019)
Background and Aims: Xerostomia is a clinical condition that can affect the quality and quantity of saliva. Saliva is considered an important factor in retention of edentulous patient's denture wearers. Thus, increasing the prevalence of xerostomia in modern societies is considered a limiting factor in the quality of denture retention. This article reviews the most common techniques of denture manufacturing in edentulous patients with xerostomia and investigates the advantages versus disadvantages of each. Materials and Methods: In this review, PubMed and google scholar search engines were searched for the following keywords: Flexible Denture, Artificial Saliva Reservoir, Hyposalivation, Hypofunction, and Xerostomia. We evaluated the flexible dentures and dentures with artificial saliva reservoirs in both jaws along with their advantages and disadvantages. 10 articles, specifically discussing complete denture fabrication in patients were selected. Conclusion: Follow-up results showed that the flexible dentures and split dentures with saliva reservoirs to be effective in improving the quality of life of these patients and therefore can be a considered as a successful treatment option in the prosthetic rehabilitation of these patients.